A solution algorithm for linear constraint equations in finite element analysis - Curiskis, J.I.; Valliappan, S. (Computers & structures, 1978)
A general solution algorithm is presented for the incorporation of a general set of linear constraint equations into a linear algebraic system; such situations arise in the application of the finite element method to a variety of physical problems. Implementation of the algorithm, without need for pre-arranging the equations, into an equation solver using Gauss elimination is developed. The method is most attractive as compared to other approaches for constrained systems.